Weather index insurance: Promises and challenges of promoting social and ecological resilience to climate change - Lu Yu; Mariya Aleksandrova (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Rural communities are particularly vulnerable to weather shocks and ecosystem decline. Traditionally, farmers have adapted to climate variability and extremes through various risk management strategies, either individually or cooperatively. However, climate change amplifies the frequency and intensity of extreme weather events and exacerbates environmental degradation processes. Market-based risk transfer instruments are now being developed as complements to these conventional risk management strategies to shield rural households from increasing climate risks. At present, risk transfer solutions play a central role in the global climate and development agenda. International- and regional-level initiatives such as the InsuResilience Global Partnership support vulnerable developing countries to increase their financial protection coverage through climate risk finance and insurance, including through innovative micro-level schemes such as weather index insurance. Over the last decade, index-based weather insurance has been gaining attention in the climate resilience discourse. These schemes compensate insured individuals based on a pre-defined weather index instead of individual losses, as with traditional types of insurance. Therefore, this instrument has several advantages, including greater time- and cost-effectiveness and reduced moral hazard risk. Although weather-index insurance holds great promise, there are several challenges in designing and promoting it in developing countries. First, on the demand side, there is a lack of accessibility to affordable insurance, especially for the poorest rural populations exposed to climate hazards. Second, on the supply side, insurance providers are facing an elevated risk of paying larger claims due to the increasing frequency and severity of weather extremes, while reinsurance services are often missing. Third, the ecological effects of implementing weather index microinsurance initiatives receive little attention in research and policy. Yet, protecting the environment and building ecological resilience are critical policy dimensions of climate risk management in rural regions, where the poor disproportionately depend on ecosystem goods and services for a living, as they often lack alternative livelihood strategies. Looking into the key challenges to microinsurance initiatives and drawing upon findings of a review of literature on weather index insurance and field research, this Briefing Paper derives recommendations for development cooperation, governments and insurers for an enhanced action agenda on climate risk insurance. The discussion is focused on the specific case of weather index insurance for the rural poor at the micro level. We emphasise the importance of enhancing knowledge on the potential positive and negative ecological effects of weather insurance schemes, and the need to develop a diverse set of climate risk management strategies for the poor, including social protection mechanisms.
Keywords: 330